2012
DOI: 10.3928/01477447-20120426-12
|View full text |Cite
|
Sign up to set email alerts
|

Value of 3-D CT in Classifying Acetabular Fractures During Orthopedic Residency Training

Abstract: The complex anatomy of the pelvis and acetabulum have historically made classification and interpretation of acetabular fractures difficult for orthopedic trainees. The addition of 3-dimensional (3-D) computed tomography (CT) scan has gained popularity in preoperative planning, identification, and education of acetabular fractures given their complexity. Therefore, the authors examined the value of 3-D CT compared with conventional radiography in classifying acetabular fractures at different levels of orthoped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 9 publications
(9 reference statements)
4
50
1
Order By: Relevance
“…Letournel's original classification system was based on plain radiographs, and there is debate whether addition of CT scans improves reliability of his classification system [4,7,15,23]. Accurate and consistent classification of acetabular fractures is essential for surgical planning.…”
Section: Validationmentioning
confidence: 99%
“…Letournel's original classification system was based on plain radiographs, and there is debate whether addition of CT scans improves reliability of his classification system [4,7,15,23]. Accurate and consistent classification of acetabular fractures is essential for surgical planning.…”
Section: Validationmentioning
confidence: 99%
“…However, clinical studies already suggest this new technology as a promising and useful option in the future [1][2][3][4][5][6][7][9][10][11][12][13]. Benefits of 3D models include reduced surgical time, decreased amount of blood loss, risk of infections and exposure to ionizing radiations.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding 3D images, one study showed that at all levels of training among orthopedic surgeons, there were benefits for the use of 3D images over that of axial CT images, with the greatest benefit among junior residents (55). Another study showed that although the use of 3D images did not significantly increase accuracy for radiologists, it did increase accuracy for orthopedic surgeons (56).…”
Section: Imaging Acetabular Fracturesmentioning
confidence: 99%
“…Although it may take a few extra minutes to construct the 3D model, we believe there are substantial benefits of higher confidence and greater accuracy (55,56). Once the 3D reconstruction is created, it should be oriented in the standard position, with the acetabulum en face and the acetabular notch directed inferiorly.…”
Section: How To Practically Classify An Acetabular Fracturementioning
confidence: 99%